2018
DOI: 10.1038/s41467-018-03382-x
|View full text |Cite
|
Sign up to set email alerts
|

Germinal center entry not selection of B cells is controlled by peptide-MHCII complex density

Abstract: B cells expressing high affinity antigen receptors are advantaged in germinal centers (GC), perhaps by increased acquisition of antigen for presentation to follicular helper T cells and improved T-cell help. In this model for affinity-dependent selection, the density of peptide/MHCII (pMHCII) complexes on GC B cells is the primary determinant of selection. Here we show in chimeric mice populated by B cells differing only in their capacity to express MHCII (MHCII+/+ and MHCII+/−) that GC selection is insensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 43 publications
7
72
0
Order By: Relevance
“…144 Remarkably, the minimal BCR affinity required for GC seeding is very low, and in the absence of competition, B cells bearing BCRs with inefficient cognate antigen binding can still receive sufficient T-cell help and seed GCs. 147 Similarly, we demonstrated that ICAMs on B cells are required for T-cell interaction with B cells; however, B cells deficient for ICAMs can still seed GCs. 93,145 In a recent study that examined whether the amount of MHCII on the surface of the B cells plays a role in GC seeding, it was found that B cells bearing two-fold less MHCII are outcompeted by WT B cells prior to GC coalescence.…”
Section: Adhe S Ivene Ss In Control Of Clonal S Elec Tion For G Ermmentioning
confidence: 57%
“…144 Remarkably, the minimal BCR affinity required for GC seeding is very low, and in the absence of competition, B cells bearing BCRs with inefficient cognate antigen binding can still receive sufficient T-cell help and seed GCs. 147 Similarly, we demonstrated that ICAMs on B cells are required for T-cell interaction with B cells; however, B cells deficient for ICAMs can still seed GCs. 93,145 In a recent study that examined whether the amount of MHCII on the surface of the B cells plays a role in GC seeding, it was found that B cells bearing two-fold less MHCII are outcompeted by WT B cells prior to GC coalescence.…”
Section: Adhe S Ivene Ss In Control Of Clonal S Elec Tion For G Ermmentioning
confidence: 57%
“…In consequence, plasmacytes, which do not divide, cannot be studied by Nojima cultures. GC B cells, which may be fragile (1) or predisposed to differentiate into plasmacytes, have a lower cloning efficiencies (~25%) than naïve or memory B cells (70–80%) (38, 43). Despite these limitations, we have found Nojima cultures to be a useful tool for BCR repertoire analysis and an effective pathway for the identification and study of “interesting” Abs (38, 40).…”
Section: Current Methods For B-cell Repertoire Analysismentioning
confidence: 99%
“…We quantitatively tested this hypothesis by generating chimeric mice in which B cells differing only by their capacity to express MHCII could compete for entry into and success within GCs. Control of MHCII expression was by haploinsufficiency, that is, B cells either were homozygous or were heterozygous for functional MHCII loci (MHCII +/+ or MHCII +/− , respectively)(43). In some instances, we fixed the initial BCR affinity in both populations by a shared VDJ knockin; in others, we allowed both populations to express the full BCR repertoires available to them (43).…”
Section: Analysis Of Gc B Cell Repertoires After Immunization With Comentioning
confidence: 99%
See 2 more Smart Citations